A taxonomic revision of the kalshoveni species-group of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae), with descriptions of six new species from Indonesia and Papua New Guinea - Kozlov, Mikhail V. (Zootaxa, 2016)
A monophyletic group of seven externally similar, grey to light brown species of the genus Nemophora Hoffmannsegg from the islands of Indonesia and Papua New Guinea, recognised as the new kalshoveni species-group, is revised. All species of this group possess an oblique light stripe, which arises from the costal margin of the forewing at 0.7–0.8 of its length towards the middle of an external wing margin. The proboscis of these species is unusually thick due to a dense cover of raised dark brown and black scales. A key to the species based on external characters and on male genitalia is provided; new species are described from the Sangir (N. humerella sp. nov.) and New Guinea (N. agassizi sp. nov., N. bistrigata sp. nov., N. dohertyi sp. nov., N. toxopeusi sp. nov. and N. stenopterella sp. nov.).